200 years of Darwin wasp research (Hymenoptera, Ichneumonidae) in Southern Lower Saxony (Germany) with an annotated checklist - Mike Kuschereitz (Contributions to Entomology)
A wide range of data was compiled from literature, insect collections and citizen science data with the aim to create an initial and preliminary regional checklist of Ichneumonid wasps for Southern Lower Saxony. In total, 1811 records of 876 Ichneumonid species were found, including 260 unpublished species records. The records originate from the last two centuries, two thirds being made in the last 90 years. The majority of data was collected by renowned Ichneumonid experts like Carl Gravenhorst, Erich Bauer and Rolf Hinz, but also by other scientists conducting surveys on ecological topics. Based on the compiled data, six Darwin wasp species could be added to the German Darwin wasp list, namely: Camposcopus ruficoxis (Schnee and Shaw, in prep.), Coleocentrus soleatus (Gravenhorst, 1829), Netelia contiguator Delrio, 1975, Netelia silvahercynia Theunert, 2021, Proclitus heterocerus (Thomson, 1888) and Tycherus acutus (Gravenhorst, 1829). It can be assumed that the communities of Darwin wasps in the two main natural regions in Southern Lower Saxony, the Weser-Leine Uplands and Harz Mountains, differ in their composition, but this cannot be confirmed with certainty due to the low resolution and the different scope of the data. Apart from poorly studied locations, future surveys should focus on under-sampled habitats and include unrevised material to expand this regional checklist and give detailed information on habitat associations of Darwin wasp species.